PENGARUH PERAN PENYULUH DAN KEARIFAN LOKAL TERHADAP ADOPSI INOVASI PADI SAWAH DI KECAMATAN MONTASIK KABUPATEN ACEH BESAR - Andrian Wira Syah Putra; Sunarru Samsi Hariadi; Harsoyo Harsoyo (Universitas Muhammadiyah Sidoarjo, 2012)
The basic method used in this research was the analytical descriptive with the quantitative approach which was suported by its qualitative side. The chosen location of the research was done on purpose that was the sub-district of Montasik (WKPP Piyeung I and WKPP Bukit Baro I) the regency of Aceh Besar. First, the second and the third hypothesis was using the multiple linear regression and the correlation, for the fourth hypothesis was using the qualitative approach. From the analysis results of multiple linear regression test which was using the Backward (model 5) in the first, the second and the third hypothesis indicated that all of the seven variables tested, three of them were instructor role variables, motivation and attitude had the positive and significant impact on innovation adoption of rice farming. With the sig value from the instructor role variables was 0.000 < 0.10, the sig value of the motivation was 0.097 < 0.10, and the sig value of the attitude was 0.004 < 0.10. For the fourth hypothesis showed the synergies between the counseling activities with the indigenous local wisdom approach towards the innovation adoption of rice farming where the extension worker and the community leaders could work together as well in the organizing of the rice planting schedule and in the process of environmental preservation in the Montasik sub-district.